2020
DOI: 10.1038/s41526-020-00115-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular impact of launch related dynamic vibrations and static hypergravity in planarians

Abstract: Although many examples of simulated and real microgravity demonstrating their profound effect on biological systems are described in literature, few reports deal with hypergravity and vibration effects, the levels of which are severely increased during the launch preceding the desired microgravity period. Here, we used planarians, flatworms that can regenerate any body part in a few days. Planarians are an ideal model to study the impact of launch-related hypergravity and vibration during a regenerative proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…This suggests further space experiments and investigations to clarify whether observed phenotype was due to space travel (48). Another recent study showed that rocket launch related vibrations and hypergravity can affect the expression of the early stress response genes in planarians during a regenerative process (49).…”
Section: Regenerationmentioning
confidence: 90%
“…This suggests further space experiments and investigations to clarify whether observed phenotype was due to space travel (48). Another recent study showed that rocket launch related vibrations and hypergravity can affect the expression of the early stress response genes in planarians during a regenerative process (49).…”
Section: Regenerationmentioning
confidence: 90%
“…In addition, researchers also conducted a series of experiments using engine vibration signal [46,47], adaptive correlation algorithm [48], frequency band peak ratio [49,50], characteristic frequency band root mean square value [51], and principal component analysisbased extraction of eigenvectors. Fault detection approaches using signal processing are studied, such as binary time series analysis of phase plane trajectory [52,53], sliding time window principal component analysis [54], fast Fourier transform [55], etc.…”
Section: Other Approaches Using Signal Processingmentioning
confidence: 99%